Management of symptomatic neonatal aortic thrombosis: When is surgery indicated? - Bryan V. Dieffenbach; Bharath D. Nath; Elisabeth T. Tracy; Heung Bae Kim (Elsevier, 2019)
Neonatal aortic thrombosis is a rare but potentially life-threatening condition. Treatment is patient-specific and may include expectant management, therapeutic anticoagulation, systemic thrombolysis or surgical thrombectomy. The majority of cases are managed non-operatively with variable success. We present two cases of acute aortic thrombosis each managed surgically with open aortic thrombectomy. These cases demonstrate that surgical thrombectomy is an effective method for the treatment of symptomatic aortic thrombosis in neonates and can prevent or mitigate permanent end-organ damage in select cases. We advocate for immediate therapeutic anticoagulation in all cases (unless contraindicated) and upfront surgical thrombectomy in cases of imminent abdominal visceral ischemia, renal failure or threatened limb. Systemic thrombolysis should be pursued in less severe cases where end-organ injury is not an immediate concern. Keywords: Neonatal aortic thrombosis, Open aortic thrombectomy